My First 5 Minutes Fairy Tales : Rapunzel - Om Books international (Bharat Om Books International, 2019)
Rapunzel was trapped in a tall tower for her whole life. Will she ever manage to escape? This is a beautiful retelling of the classic fairy tale Rapunzel in Hindi. Vibrant, captivating illustrations and simple Hindi text will spark the childrens imagination, develop speech & language skills, and encourage them to read books.
Keywords: Traditional Literature - FairyTales -- Traditional Literature - FairyTales